CHARACTERISTICS OF LATERITE NICKEL DEPOSITS, MODELLING OF DEPOSITS AND ESTIMATION OF GRADES AND RESOURCES USING 3D ORDINARY KRIGING BLOCK METHOD IN NORTH KONAWE, SOUTHEAST SULAWESI - Munthe, Harlen
Laterite nickel deposits originate from the intensive weathering of ultramafic rocks over a long period, allowing leaching, dissolving, and elemental accumulation. The research area is in North Konawe Regency, Southeast Sulawesi Province, located in an ophiolite complex with peridotite lithology of lherzolite type with an area of ±0,7x0,7 km2. This study aims to determine the characteristics of laterite nickel deposits, deposit modeling, grade estimation, and resource calculations. The primary data is secondary drilling logging data, including assays, collars, surveys, geology, and other supporting data. The profiles of laterite deposits formed are generally limonite, saprolite, and bedrock, distinguished by their geochemical and mineralogical properties. The geochemical change from bottom to top progressively from silicate dominance to iron dominance is a product of the laterization process. The saprolite zone is characterized by supergene enrichment of Ni elements along the fracture. In contrast, the limonite zone is characterized by the enrichment of residual Fe, Al2O3, and Cr2O3 and the enrichment of MnO and Co supergenes at the bottom of this zone. This study also modeled the geometry of laterite nickel deposits in 3-dimensional blocks using the ordinary kriging (OK) method. The OK method will estimate the grade in each block based on the known grade value in each borehole by taking into account the spatial correlation in the form of a variogram. The variogram selection is used to maximize the results of the content estimation, which is done by determining the maximum continuity in all horizontal directions. The resource calculation consists of volume, tonnage, and average grade, which are classified based on each block's kriging variance (KV) value. The higher the KV value, the lower the geological confidence due to the significant error. For Ni content, the total inferred resource tonnage is 9,460,927 tons, indicated at 2,732,630 tons, and measured at 2,350,776 tons with a Ni content of 130,100 tons. Regarding Fe content, the inferred resource is 7,271,524 tons, indicated at 4,039,323 tons and measured at 2,817,307 tons with a Fe content of 5,277,778 tons.